The Effect of Capital Structure, Profitability and Company Size on Value of Companies In The Automotive Industry Sector Listed on IDX 2014-2018 - Wahyu Leman; Iman Sofian Suriawinata; Irvan Noormansyah (Indonesian Journal of Business, Accounting and Management (IJBAM), 2020)
This study aims to determine the effect of capital structure on firm value, the effect of profitability on firm value, and to determine the effect of company size on firm value in the automotive industry sector listed on the Stock Exchange in 2014-2018. This study aims to determine the causal correlation between 2 or more variables. Meanwhile, based on the type of data, this research is categorized as a causality quantitative study, namely research to describe the state of the company which is carried out by analysis based on the data obtained. The dependent variable in this study is firm value, while the independent variable is Capital Structure, Profitability, and Company Size. In this study using secondary data obtained from Automotive Industry Sector Companies Listed on the IDX in 2014-2018. The objects in this study are capital structure (X1), profitability (X2) and company size (X3) and their influence on firm value (Y). The population used in this study were all manufacturing companies in the automatic industrial sub-sector listed on the Indonesia Stock Exchange, totaling 18 companies. Sampling in this study was carried out using purposive sampling method. The results of this study indicate that first, capital structure affects firm value. This indicates that increasing DER will result in good management, which can increase company profits, thereby increasing company value. Second, profitability has a negative effect on firm value. This shows that even though the company has suffered losses in the past few years, investors have confidence in the business prospects of companies in the automotive industry sector in the future if managed properly and professionally. Third, company size has a negative effect on firm value, meaning that the bigger a company is, the less efficient it is in managing its resources, and the more complicated